Analysis of the causes of defects in ground floor systems of residential buildings. Issue 2 (25th January 2023) - Gurmu, Argaw Tarekegn; Krezel, Adam; Mahmood, Muhammad Nateque
Abstract: The objective of this research is to analyse the interactions among the causes of defects in ground floor systems of low-rise residential buildings, and on that basis, to identify the most significant causes. The data used in this study was extracted from engineering inspection reports of 250 residential buildings in Melbourne, Australia. Association rule mining technique was used to investigate the relationships among the causes of the defects in the ground floor slab systems and to generate support, confidence and lift values. social network analysis was then carried out using the confidence values and the most significant causes of the ground floor slab defect were identified. Inadequate site drainage and soil drainage, with the out-degrees centrality of 4.84 and 4.56, respectively, were found to be the two main causes of distress in ground floor slabs of the residential buildings. On the other hand, landscaping related problem was found to have the lowest out-degree centrality value (1.60) which implies that the occurrence of poor landscaping on certain residential premises might not be the major cause for defects in the slab. The output of this research can provide useful information regarding the causes of cracks in ground floor slab systems of residential buildings. Understanding the causes of the defects, in turn, can help developers and contractors to take appropriate corrective actions or to develop strategies to reduce the occurrence of defects in newly constructed houses.